1999
DOI: 10.1007/s001250051216
|View full text |Cite
|
Sign up to set email alerts
|

An uncoupling protein 2 gene variant is associated with a raised body mass index but not Type II diabetes

Abstract: The regulation of body fat equilibrium in mammals depends on a balance between diet and energy expenditure. Energy expenditure occurs as a result of a combination of resting metabolic rate, physical exercise and non-shivering thermogenesis. It has become increasingly evident that even small calorific inequalities can lead to an increase in fat storage and obesity. There is also an intimate association between increasing body weight and Type II (non-insulin-dependent) diabetes even in populations in which obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
71
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 28 publications
12
71
3
Order By: Relevance
“…The ID gene polymorphism located in exon 8 of 3 0 UTR of UCP2 gene have been Fig. 2 a Hex generated GHreceptor-ghrelin complex for wild type, b Hex generated GHreceptor-ghrelin complex for mutant type previously reported to be associated with energy expenditure (Walder et al 1998), increased BMI (Cassell et al 1999), and accumulation of fat tissue (Pedersen et al 2005). In our study UCP2 ID showed protective effect.…”
Section: Discussionsupporting
confidence: 59%
“…The ID gene polymorphism located in exon 8 of 3 0 UTR of UCP2 gene have been Fig. 2 a Hex generated GHreceptor-ghrelin complex for wild type, b Hex generated GHreceptor-ghrelin complex for mutant type previously reported to be associated with energy expenditure (Walder et al 1998), increased BMI (Cassell et al 1999), and accumulation of fat tissue (Pedersen et al 2005). In our study UCP2 ID showed protective effect.…”
Section: Discussionsupporting
confidence: 59%
“…113,114 Additional UCP2 exon SNPs have been associated with basal metabolic rate or 24-h energy expenditure. [114][115][116] The phenotypic associations have not been confirmed in other populations. 117,118 UCP2 SNPs do not seem to regulate weight change.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 83%
“…An association between the UCP2 exon 8 variant and body mass index was measured in two groups of South Indians [199]. This association was not observed in British subjects, but the UCP2 genotype of obese women was correlated with the serum leptin concentration, suggesting that the UCP2 variant may affect susceptibility to weight gain by influencing regulation of leptin [199]. No significant association between UCP2 polymorphisms and obesity or type II diabetes was noted by others [147,163,164,194,196,[198][199][200].…”
Section: Linkage and Association Studies Of Human Ucp Genesmentioning
confidence: 88%
“…Walder et al [197] calculated that UCP2 gene polymorphisms were genetically associated with sleeping energy expenditure in Pima Indians, whereas no such association was found in a Scandinavian cohort [195]. An association between the UCP2 exon 8 variant and body mass index was measured in two groups of South Indians [199]. This association was not observed in British subjects, but the UCP2 genotype of obese women was correlated with the serum leptin concentration, suggesting that the UCP2 variant may affect susceptibility to weight gain by influencing regulation of leptin [199].…”
Section: Linkage and Association Studies Of Human Ucp Genesmentioning
confidence: 99%